Boundary management in projects: Antecedents, activities and performance - Lisbeth Brøde; Perttu Dietrich (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2010)
Despite increasing interest among practitioners and the recent scientific explorations on the dynamics of boundary management in project and team contexts, the existing studies seems to lack empirical understanding on the factors that explain the boundary management behavior of project managers. The purpose of this study is to analyze how the three antecedent factors - cross-functional participation, embeddedness and top management control - are related to four different types of boundary management activities practiced by project managers, namely coordinating, enabling, reporting and guarding. Based on the sample of 236 projects, the results show that embeddedness and top-management control have positive influence on boundary-management activities and crossfunctional participation has both positive and negative contribution to boundary management activities. Furthermore, the results reveal that boundary management activities have both positive and negative influence on project performance. Contributions of the research are discussed, as well as practical implications, limitations, and directions for future research.
Keywords: 330; boundary management; project team; embeddedness; crossfunctional participation; top-management control; Projektmanagement; Arbeitsgruppe; Produktinnovation